2021
DOI: 10.1186/s40337-021-00462-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on eating disorder referrals and admissions in Waikato, New Zealand

Abstract: Background Several countries have reported increased demand for eating disorder services during the COVID-19 pandemic, particularly for adolescents. Within New Zealand, anecdotal and media reports suggest similar changes but are limited in scope and detail. We assessed eating disorder service demand in the Waikato district in relation to the COVID-19 pandemic. Methods We retrospectively analysed records of eating disorder admissions and referrals f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 22 publications
6
36
1
Order By: Relevance
“…Second, the pandemic also influences eating behavior in the general population [5,6]. Finally, the number of adults with eating disorders has reportedly increased [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the pandemic also influences eating behavior in the general population [5,6]. Finally, the number of adults with eating disorders has reportedly increased [7].…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, eating behaviors and body image have been reportedly associated with several factors related to the COVID-19 pandemic, such as fear, anxiety, and intolerance of uncertainty [5,6]. Furthermore, a report suggested an increase in patients with eating disorders since the COVID-19 pandemic [7]. Although these reports, which are from Europe, the Middle East, New Zealand, and the United States, suggest that the COVID-19 pandemic may increase the prevalence of eating disorders, there have been few reports showing such an increase in eating disorders in the Asian region, including Japan.…”
Section: Introductionmentioning
confidence: 99%
“… a Allowed for participants to indicate more than one lifetime or current ED; N adds to more than reported ED sample size. b Hansen et al ( 2021 ) counted participants identifying as dual ethnicities (four outpatients and one inpatient) twice, as per New Zealand census guidelines. c Kim et al (2021) (1) reported prevalence of both clinical and non‐clinical ED's in their sample.…”
Section: Resultsmentioning
confidence: 99%
“… b Hansen et al ( 2021 ) counted participants identifying as dual ethnicities (four outpatients and one inpatient) twice, as per New Zealand census guidelines. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation